Pengaruh Sustainability Report, Free Cash Flow, dan Pertumbuhan Penjualan terhadap Kinerja Keuangan - Badriyah Dwi Lestari; Anwar Hariyono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study focuses on analyzing the influence of sustainability reports, free cash flow, and sales growth on the financial performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Financial performance is measured using Return on Assets (ROA) as the main indicator to assess a company's ability to generate profits from its total assets. This study uses a quantitative approach with multiple linear regression analysis to examine the relationship between variables. The data used are documentary data with secondary data sources obtained from financial reports and company sustainability reports. A purposive sampling technique was applied to determine the research sample based on certain criteria, resulting in 95 observational data. The results show that free cash flow and sales growth have a significant influence on financial performance, indicating that the company's ability to generate free cash and increase sales directly contribute to performance improvements. Conversely, sustainability reports were not proven to have a significant effect on financial performance, so sustainability disclosure has not been a determining factor in increasing the ROA of energy sector companies during the study period.